2003
DOI: 10.1038/sj.bdj.4810184
|View full text |Cite
|
Sign up to set email alerts
|

The interdisciplinary management of hypodontia: the relationship between an interdisciplinary team and the general dental practitioner

Abstract: This paper will illustrate how the general dental practitioner can provide care for patients with hypodontia. It will demonstrate how an interdisciplinary team works for hypodontia patients and, in particular, for those with severe hypodontia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 2 publications
0
27
0
1
Order By: Relevance
“…It incorporates consultants from paediatric, restorative, orthodontics and oral and maxillofacial surgery and aims to ensure appropriate timing and management at each stage of treatment. 16 Similar combined, multidisciplinary clinics are held in other dental hospitals of the United Kingdom. 1,17,18 Hobkirk et al 18 presented demographic data for those attenders, but there appears to be a dearth of contemporary information regarding treatment planning and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…It incorporates consultants from paediatric, restorative, orthodontics and oral and maxillofacial surgery and aims to ensure appropriate timing and management at each stage of treatment. 16 Similar combined, multidisciplinary clinics are held in other dental hospitals of the United Kingdom. 1,17,18 Hobkirk et al 18 presented demographic data for those attenders, but there appears to be a dearth of contemporary information regarding treatment planning and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Patient related factors include age, attitude and expectations; orthodontic factors include the severity of the hypodontia, type, and degree of malocclusion; further consideration also has to be given to the occlusion and the aesthetics. 7,[18][19][20][21] There have been numerous studies investigating resin-bonded bridges (RBBs) since their introduction almost 30 years ago. 22,23 It has been shown that they can provide long term service, [24][25][26][27][28] patients are highly satisfied with the results, 29 and they are an acceptable alternative to conventional bridgework.…”
Section: Introductionmentioning
confidence: 99%
“…The primary teeth act as ideal space maintainers that prevent the undesirable movement of adjacent teeth, which may cause difficulties in the placement of implants or fixed prosthesis [15]. The longevity of the retained primary teeth with no permanent successors is uncertain.…”
Section: Discussionmentioning
confidence: 99%